2016
DOI: 10.1038/ijir.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sexual outcomes after holmium laser enucleation of the prostate: which patients could benefit the most?

Abstract: Assess rate and predictors of erectile function (EF) outcomes at long-term follow-up (FU) after holmium laser enucleation of the prostate (HoLEP). Cross-sectional analyses were performed on 135 patients with a mean FU of 12 years post HoLEP. Patients completed both a baseline and a FU International Index of Erectile Function (IIEF)-EF domain and the International Prostatic Symptoms Score (IPSS). Postoperative EF outcomes, including rate and predictors of EF improvement considering minimal clinically important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
5
12
0
2
Order By: Relevance
“…Similar results were also obtained by Capogrosso et al. [31] in patients undergoing enucleation procedure.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also obtained by Capogrosso et al. [31] in patients undergoing enucleation procedure.…”
Section: Discussionsupporting
confidence: 89%
“…Long-term sexual outcomes showed that the patients with more severe preoperative urinary symptoms and ED would be more likely to have a clinically meaningful EF improvement, which was attributed to a persistent amelioration of LUTS. 31 For the patients without preoperative ED, a relatively small, but still significant, negative effect on erections in the early period after HoLEP was reported. 8 Thus, it is still controversial for the impact on sexual functions between enucleation and resection of prostate.…”
Section: Discussionmentioning
confidence: 95%
“…Long‐term sexual outcomes were published by Capogrosso et al. (2016). The group reported the IIEF‐EF outcomes of 135 sexually active men with a mean follow‐up of 152 months.…”
Section: Erectile Functionmentioning
confidence: 99%